Comparison between infiltration and inferior alveolar nerve block anesthesia in extraction of non-vital mandibular posterior teeth (prospective clinical study) - Hussein, Rozh M .; Muhammad, Dilman N.; Omar, Othman A. (Zanco Journal of Medical Sciences (ZJMS), 2014)
Background and objective: Infiltration anesthesia for the posterior region of the mandible has been routinely avoided because of its questionable effectiveness related to the dense cortical bone of the mandible. The aim of this study was to evaluate the effectiveness of infiltration anesthetic technique on mandibular posterior non-vital teeth. Methods: Forty four patients aged between 13and 73 years who attended the Department of Oral and Maxillofacial Surgery in the College of Dentistry, Hawler Medical University for extraction of posterior non vital tooth were included in this study. For the infiltration anesthetic technique, patient’s approval was taken. The patients were equally divided into two groups. Group (1) received 0.6 ml out of 1.8 ml of 2% lidocaine with 1:80000 adrenaline injection bucally and the same amount infiltration lingually opposite the intended tooth. Group (2) received 1.5 ml out of 1.8 ml of 2% lidocaine with 1:80000 and the remaining 0.3 ml was injected for long buccal nerve anesthesia. Results: In group (1), 68.2% had no pain during extraction, showed statistically highly significant difference (P = 009). Gender showed no significant difference. In group (2), 100 % of the patients had no pain during extraction. Conclusion: Infiltration anesthesia for non-vital mandibular molars is effective as a substitute for inferior alveolar block technique.